Token-Regulierung in Europa: Vergleich von TVTG (Liechtenstein) und MiCAR (EU) aus Unternehmenssicht - Carl B. Welker (IU Internationale Hochschule, 2024)
– Since the first bitcoins were mined in 2009, a large number of blockchains and a vast number of different tokens have been created on the basis of distributed ledger technologies (DLT). The Web3 ecotope, with its essential characteristics such as decentralized transactions and anonymity, is functioning and is preparing to attract billions of dollars in further demand and absorb investor funds. For companies that want to become active on the web3, there is also the question of a generally applicable and enforceable legal framework that covers the most diverse fields of application of the token economy, blockchains with their smart contracts, tokens as universally usable economic objects, token emissions and token trading. A DLT Act was enacted for the first time in the Principality of Liechtenstein in 2019: The "Token- und VTDienstleister-Gesetz" (TVTG, Token and DLT Service Provider Act). In 2023, the EU followed suit with Regulation (EU) 2023/1114 "Markets in Crypto-Assets Regulation, MiCAR" as a template for legislative amendments in all EEA countries. This discussion paper examines the aforementioned laws in terms of how they reflect new Web3 realities, whether they are suitable in terms of their objectives and approach to promote new digital markets and how tokens are understood as legal objects.
Keywords: G18; G20; K22; K23; K24; L26; M13; O32; O33; O35; 650; Web3; Distributed Ledger Technologies; Blockchain; Tokenization; Regulation